Pengaruh Perceived Usefulness, Perceived Ease of Use, dan Subjective Norm terhadap Purchase Intention Melalui Attitude Pengguna OLX: (Studi Kasus pada Mahasiswa UST Yogyakarta) - Nugraha, Tommy Wiguna; Udayana, Ida Bagus Nyoman; Lukitaningsih, Ambar (Jurnal Bingkai Ekonomi (JBE), 2021)
This study aims to determine the effect of perceived usefulness, perceived ease of use and subjective norms on purchase intention through the attitude of OLX users (Case study: On UST Yogyakarta Students). The population in this study were all students of UST Yogyakarta who used the OLX application. The number of the study population is unknown. The sample in this study is part of the target population is all students of UST Yogyakarta. The results of this study indicate that Perceived usefulness has a positive and significant effect on attitude and purchase intention, Perceived ease of use has a positive and significant effect on attitude and purchase intention, Subjective norm has a positive and significant effect on attitude and purchase intention, Attitude has a positive and significant effect on purchase. intention.